LITERATURE STUDY OF PYTHAGORAS METHOD IN SOLVING PROBLEMS OF EINSTEIN’S SPECIAL THEORY OF RELATIVITY - Sanusi, Erda Nasitah; Haryadi, Rudi (EduFisika: Jurnal Pendidikan Fisika, 2022)
The particular theory of relativity stems from the discovery of a physicist named Albert Einstein. The difficulties in physics have been described by Sugiyana, “Physics is one of the subjects that cause difficulties for students. This happens because physics is considered a complex subject with many similarities. The limited ability of students and lack of interest in physics has also added to the difficulties in studying physics. Using the fast method is one of the categories for calculating quickly. One fast method is the Pythagorean method, which can solve particular relativity questions.